Indicadores clínicos e epidemiológicos da tuberculose no Brasil, 2001 - 2020: dinâmica espacial, tendência temporal e impacto da pandemia de COVID-19 - Souza, Mariana do Rosário (2024)
Tuberculosis (TB) is a severe and chronic infectious disease, cause by the bacillus Mycobacterium tuberculosis. Around 10.6 million people fall ill with TB around the world annually and, despite it being a curable disease, 1.6 million people die each year due to clinical complications of this disease. In Brazil, regional disparities can influence TB prevalence and mortality and poorer regions, such as the Northeast, may be more affected by the disease. Considering this, we aimed herein to assess the spatial and temporal dynamics of clinical and epidemiological indicators of tuberculosis and the impact of the COVID-19 pandemic on diagnoses of the disease in Brazil. To this end, an ecological and time series study was conducted with data obtained from the Brazilian government's public platforms, the Notifiable Diseases Information System (SINAN) and the Brazilian Institute of Geography and Statistics (IBGE) and with pulmonary tuberculosis (PTB) indicators from the nine states of the Northeast region. To assess the impact of the pandemic on TB cases, the P-score was calculated, considering the number of expected cases and according to the average of new cases registered monthly in the five years prior to the pandemic. For spatial analysis, global and local Moran indices were applied, and spatiotemporal scanning statistics were used to detect high-risk clusters. Temporal trends were assessed using a segmented linear regression model. After the outbreak of the COVID-19 pandemic in 2020, there were reductions in TB (-8.3%) and PTB (- 8.1%) diagnoses in Brazil and interrupted time series analyzes corroborated this decline from March 2020. Concerning the disease indicators in the Northeast region, 426,110 cases of PTB were reported between 2001 and 2020, with a predominance of cases in the age group of 20-39 years (43.04%), among non-whites (54.65%) and men (66.04%). Furthermore, the incidence and mortality coefficient in the region was 35.94 and 1.15/100 thousand inhabitants, respectively. The highest incidence and mortality rates were observed in the state of Pernambuco (55.66 and 2.03/100 thousand inhabitants, respectively). Contradictorily, Sergipe has the highest proportion of cures (72.05%) and abandonment (12.77%). Additionally, a stable temporal trend was observed in the case detection coefficient in the region. Conversely, the mortality rate showed an increasing trend in this period (APC = 17.4% per year) and this increasing trend was observed in all states. Impressively, there was stability in the proportion of abandonment and a decreasing trend in the proportion of cured patients. PTB has a heterogeneous distribution in the Northeast region, but with high-risk spatiotemporal clusters, mainly in Bahia, Ceará, Maranhão and the coast of Alagoas and Pernambuco. Taken together, these data report an insidious and worrying scenario regarding TB in Brazil. In addition, our analyzes demonstrated the severe impact of the COVID-19 pandemic, with a reduction in TB and PTB diagnoses in Brazil and its regions. The stability in the incidence rate, associated with the increase in the mortality rate and the drop in the proportion of cured people, highlights the deficiencies in TB control and puts Brazil's goal for the “End TB strategy” agreed with the WHO at risk.